Structural peculiarities of one-component firmonyms in the English language - Arseenko, S.G.; Vovk, N.A.; Shevchenko, N.V. (Культура народов Причерноморья, 2013)
In the article the authors analyze structural characteristics of one-component firmonyms in the English language. The term "firmonym" more adequately reflects the signs of the category of the proper names. One-word firmonyms are divided into two groups from the structural point of view. The first one consists of simple names, made up of one word, which cannot be separated into lexemes. The rest firmonyms are complex structures. They are represented with six models. To illustrate this English factual material is used. Key words: ergonym, firmonym, structure